Measures adopted for weight reduction among overweight and obese adults: a community based cross sectional study - A., Radhakrishnan; R. C., Karthik; Arumugam, Balaji; Ezhilvanan, M. (International Journal Of Community Medicine And Public Health, 2020)
Background: Worldwide obesity prevalence has nearly doubled since 1980. Current guidelines recommend that “overweight” and “obese” individuals lose weight through engaging in lifestyle modification involving diet, exercise and other behaviour changes. It is necessary to prevent obesity so that the subsequent complications can be prevented. Methods: This community based cross sectional study was conducted in the field practice area of tertiary medical college from June 2019 to August 2019. Totally 154 participants enrolled in the study. Only those individuals who had body mass index (BMI) of more than 23 kg/m2 were included in the study. Results: Majority of the study subjects 57.1% (88) belonged to the age group of 21-40 years. We included only overweight and obese adults in the present study. In this study, 61% (94) of the study population belonged to obese- I category while 33.8% (52) belonged to obese- II and only 5.2% (3) of study population were overweight. Only 43% (66) of the study population had adopted some measures to reduce their weight. Out of these majority 69.7% (46) preferred walking while 12.1% (8) preferred jogging for reducing weight. Mean days of walking adopted was 3.7 days and mean minutes per day was 29.67 minutes. Conclusions: As seen in this study more than half of the study population had not taken any measures for weight reduction. Increased health awareness will improve their level of active participation in the weight reduction program such as diet modification and physical exercise promotes weight loss and weight maintenance.